2018
DOI: 10.1002/gps.4913
|View full text |Cite
|
Sign up to set email alerts
|

Memory assessment services and health‐related quality of life: 1‐year follow‐up

Abstract: Improvements in HRQL observed at 6 months are maintained up to 1 year after the first MAS appointment, more so among those who receive a diagnosis of dementia. Continued follow-up will determine if the improvement is even longer lasting.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 26 publications
(52 reference statements)
0
6
0
Order By: Relevance
“…Patients' mean health-related quality of life improved in the first 6 months irrespective of diagnosis. Another cohort study 106 found that self-reported health-related quality of life improved in all study participants over the first year after their initial appointment at a MAS. People with a diagnosis of dementia saw greater improvement in health-related quality of life than people with MCI or no diagnosis.…”
Section: Memory Clinics/memory Assessment Servicesmentioning
confidence: 93%
See 2 more Smart Citations
“…Patients' mean health-related quality of life improved in the first 6 months irrespective of diagnosis. Another cohort study 106 found that self-reported health-related quality of life improved in all study participants over the first year after their initial appointment at a MAS. People with a diagnosis of dementia saw greater improvement in health-related quality of life than people with MCI or no diagnosis.…”
Section: Memory Clinics/memory Assessment Servicesmentioning
confidence: 93%
“…Memory clinics or MASs were investigated in 16 studies 16,46,48,49,70,77,[102][103][104][105][106][107][108][109][110][111] (Table 9).…”
Section: Memory Clinics/memory Assessment Servicesmentioning
confidence: 99%
See 1 more Smart Citation
“…This study focuses on HRQL reported by the patient. Proxy‐reports by their carer are reported elsewhere . Patient questionnaires included disease‐specific (DEMQOL) and generic (EQ‐5D‐3 L) HRQL outcomes.…”
Section: Methodsmentioning
confidence: 99%
“…All of the available HRQL instruments for people with dementia were originally developed using psychometric methods based on Classical Test Theory (CTT) [30] and although widely used at the time, instruments developed using CTT have a number of weaknesses (see [22] for an overview). Firstly, they generate scales that at best are ordinal rather than equidistant interval scales.…”
Section: Psychometric Approachesmentioning
confidence: 99%